PRODUCTIVITY OF RICE-GROUNDNUT CROPPING SYSTEM UNDER INTEGRATED NUTRIENT MANAGEMENT - E.ARUNA*, G. KARUNA SAGAR; A. PRATAP KUMAR REDDY (The Journal of Research ANGRAU, 2019)
The experiment was conducted during Kharif and Rabi seasons of 2016 - 18 to record the performance of rice under integrated nutrient management and residual effect on succeeding groundnut crop and productivity of the system.The experiment was laid out in RBD during Kharif with rice variety ‘BPT-5204’ and sown with six treatments viz., T1 - 50 % RDF + 50 % N vermicompost; T2 - 75 % RDF + 25 % N vermicompost; T3 - 100 % RDF, T4 - 100 % RDF + 25 % N vermicompost; T5 - 100 % RDF + 50 % N vermicompost; and T6 - 150-60- 40 kg NPK ha-1. Residual effect on succeeding groundnut crop was studied by dividing each rice plot into four plots.Groundnut variety ‘Dharani’ was sown in December with four treatments viz., F1 - No fertilizers; F2 - 50 % RDF; F3 - 75 % RDF and F4 - 100 % RDF. Pooled data of Kharif rice indicated higher grain yield (5103 kg ha- 1) with the application of 150-60-40 kg NPK ha-1 which was on par with 100% RDF + 25 % N through vermicompost (4513 kg ha-1) and 100% RDF + 50 % N through vermin compost (4579 kg ha-1).Higher pod yield of succeeding rabi groundnut (2891 kg ha-1) was obtained with the application of 100% RDF+50 % N through vermicompost. Higher system productivity was recorded (10,127 kg ha-1) with the application of 150-60-40 kg ha-1 followed by the application of 100% RDF+ 50% N through vermicompost (10,020 kg ha-1) to preceding rice.